Pengaruh Motivasi Kerja Dan Kepemimpinan Terhadap Kinerja Pegawai Kecamatan Pondok Aren Kota Tangerang Selatan - Beni Priyadi Saputra; Mohamad Safi’i (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The aim of the research is to find out how much influence work motivation and leadership have on employee performance in Pondok Aren District, South Tangerang. The method used is an associative research method with a quantitative approach. The sampling technique used a sampling formula, and obtained a sample of 76 respondents. Data analysis uses validity tests, reality tests, classical assumption tests, descriptive analysis, quantitative analysis, correlation coefficient, coefficient of determination (KD), and hypothesis testing. The research results show that there is a positive and significant influence between work motivation and performance. Where the simple linear regression equation Y = 25.840 + 0.411 X1. The correlation value is 0.441 (Very Strong). The coefficient of determination value is 61.3%. The t value is 25.840 > t table 1.666, with a significance of 0.000 < 0.05. Leadership has a positive and significant effect on employee performance. This can be proven from the simple linear regression equation Y = 21.311 + 0.516 X2. The correlation value is 0.516 (Very Strong). The coefficient of determination value is 45.3%, the t value is 21.311 > t table 1.666 with a significance of 0.000 < 0.005. Simultaneously, work motivation and leadership have a positive and significant effect on employee performance in Pondok Aren District, South Tangerang. This can be proven from the multiple linear regression equation Y = 16.272 + 0.205 X1 + 0.425 X2, correlation value of 0.670 (Very Strong). The coefficient of determination value is 29.4%, the F value is 15,481 > 2.73 with a significance level of 0.000 < 0.05.